Trade linkages and firm value: Evidence from the 2018 US-China trade war - Yi Huang; Chen Lin; Sibo Liu; Heiwai Tang (Graduate Institute of International and Development Studies, 2018)
On March 22, 2018, Trump proposed to impose tariffs on up to 50 billion of Chinese imports leading to a significant concern over the "Trade War" between the US and China. We evaluate the market responses to this event for firms in both countries, depending on their direct and indirect exposures to US-China trade. US firms that are more dependent on exports to and imports from China have lower stock and bond returns but higher default risks in the short time window around the announcement date. We also find that firms' indirect exposure to US-China trade through domestic input-output linkages affects their responses to the announcement. These findings suggest that the structure of US-China trade is much more complex than the simplistic view of global trade that engendered Trump's "Trade War" against China.
Keywords: F10; G12; G14; O24; 330; Stock returns; event study; trade policy; offshoring; input-output linkages; global value chains